THE EDUCATIONAL ROLE OF THE QAZAQ NEWSPAPER (1913 – 1918) - Ayakoz Kuttyzholova; Milen Filipov (Езиков свят)
The Qazaq newspaper played a critical role in reviving the Kazakh national identity. It was the first socio-political media outlet produced in the Kazakh language, one of the deepest and strongest roots of contemporary Kazakh journalism. The Kazakh National Intelligentsia understood that, without education and language, protecting Kazakhs’ interests was doomed to failure. Kazakh people’s illiteracy was the main vulnerability of the. Therefore, new education was needed to relieve Kazakh people from illiteracy and direct them toward the perspective of Kazakh independence. This study aimed to explore the importance of education in The Qazaq during 1913-1918. To achieve this goal, the research focused on the quantity of coverage of issues such as education, language, religion, and tradition. The Qazaq’s primary function was to educate people via media by reporting on crucial problems in Kazakh education at the time. The newspaper covered issues such as education, religion, illiteracy among Kazakh people, scholarships for poor Kazakh children, schools and teaching problems; training of teachers; tuition for schools, exchanging programs abroad, modernization of school programs, publishing of textbooks for schools; funding of building new schools, religion, schools for Kazakh girls and training of female teachers, organized a boarding school for students, teaching methodologies and teaching in the Kazakh language, and syllabus for primary and high schools.